SMYD2 epigenetically activates BMP4/SMAD1/5/8/ID3 axis to enhance cancer stem cell properties and drive sorafenib resistance in hepatocellular carcinoma - Shanshan Wang; Weicheng Wu; Zhen Shi; Mei Bin; Fengwei Zhang; Long Cai; Kaiqing Lin; Zhihui Li (Neoplasia: An International Journal for Oncology Research)
Background: Drug resistance prominently hampers the effects of sorafenib in hepatocellular carcinoma (HCC). Epigenetics play important roles in drug resistance. However, the contributions of SET And MYND Domain Containing 2 (SMYD2) to sorafenib resistance in HCC remain unknown. This study is aimed at elucidating the role and mechanism of SMYD2 in sorafenib resistance of HCC. Methods: Using our well-established sorafenib-resistant hepatocellular carcinoma (HCC) cell lines and xenograft mouse models, we evaluated SMYD2 expression levels. To investigate the biological functions of SMYD2, we conducted a series of functional assays in vitro and in vivo. Transcriptomic profiling via RNA sequencing (RNA-seq) was performed to identify downstream targets of SMYD2. Additionally, chromatin immunoprecipitation (ChIP) assays were employed to elucidate the molecular mechanism. Correlating SMYD2 and target gene expression patterns with clinical outcomes in HCC patients was investigated. Results: SMYD2 expression was significantly elevated in sorafenib-resistant HCC cells compared with parental cells. Knockdown or overexpression of SMYD2 substantially inhibited or enhanced, respectively, HCC stemness and sorafenib resistance. Mechanistically, SMYD2 promoted BMP4 expression via the maintenance of mono-methylation of histone 3 lysine 4 (H3K4me1) and di-methylation of histone 3 lysine 36 (H3K36me2) modification of its promoter. Meanwhile, knockdown or inhibition of BMP4 suppressed the stemness of sorafenib-resistant cells, inhibited the activation of SMAD1/5/8 (R-SMADs), and decreased the expression of inhibitor Of DNA binding 3 (ID3) gene. Moreover, BMP4 addition or ID3 reconstruction can partly reverse the effect caused by repression of SMYD2 or BMP4. HCC patients with positive co-expression of SMYD2/BMP4 or SMYD2/ID3 or SMYD2/BMP4/ID3 exhibited the worst prognosis. Conclusions: Our study reveals that SMYD2 is an important epigenetic mediator that activates BMP4/R-SMADs/ID3 axis, leading to enhanced stemness and sorafenib resistance. Thus, SMYD2 might represent a potential biomarker and future epigenetic therapeutic target for sorafenib resistance of HCC.